The Oklahoma State Constitution - Adkison, Danny Mark, 1950-; Palmer, Lisa McNair; Oklahoma (New York, NY : Oxford University Press, 2020)
In 1907, William Jennings Bryan described the proposed constitution for Oklahoma as 'the best constitution in the United States today.' An enduring characteristic of Oklahoma's constitution has been its faith in direct democracy and its root in Progressive Era politics. This volume traces the historical formation and constitutional development of the State of Oklahoma. It provides commentary and analysis on the intent, politics, social and economic pressures, and the legal decisions that shaped and enhanced the Oklahoma constitution since it was adopted in 1907. The text gives a broad understanding of state constitutional law within the context of Oklahoma's constitutional evolution.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 25, 2020).
Keywords: Oklahoma; Constitutions -- Oklahoma; Constitutional law -- Oklahoma; Constitutional history -- Oklahoma; Law; Laws of specific jurisdictions & specific areas of law